ELDER ABUSE DECISION SUPPORT SYSTEM - Conrad, K.J. (Innov Aging, 2017)
Objectives. The Elder Abuse Decision Support System (EADSS) was designed to meet the critical need for improved methods for assessment and substantiation of elder mistreatment, using a web-based system with standardized assessment measures. Methods. Six Illinois agencies participated in the field test. One-year pre/post analyses assessed substantiation results, using Illinois’ standard investigation procedure as a comparison. Pre/post acceptability was assessed with caseworkers. Focus groups with APS staff examined users’ experiences. Validity of measures was assessed using Cronbach’s alpha and receiver operator characteristic curve analyses with final substantiation decision as criterion. Results. Increased substantiation of abuse was found. Regarding acceptability, the two systems were found to have differing strengths and weaknesses. Outcome measures had high validity estimates while focus groups indicated directions for improvement. Significance. This study was a successful proof of concept that data collected in the field would be useful for clinical purposes as well as for research.